Vector delivery-dependant effect of human tissue plasminogen activator signal peptide on vaccine induction of T cells - Hanke, T; Ondondo, B; Abdul-Jawad, S; Roshorm, Y; Bridgeman, A (Sci Forschen, 2016)
Attachment of the human tissue plasminogen activator signal peptide (tPA-SP) to a variety of proteins has enhanced the induction of both antibody and cellular immune responses in animal models. Here, as part of a continuing effort to improve HIV-1 vaccine immunogenicity, we sought to determine whether or not addition of optimized tPA-SP improves the magnitude and functionality of T cells elicited by vaccines expressing protein HIVconsv derived from highly conserved regions of the HIV-1 proteome. The HIVconsv vaccines were vectored by plasmid DNA, non-replicating simian (chimpanzee) adenovirus ChAdV63 and non-replicating poxvirus MVA. We found that addition of the tPA-SP increased levels of intracellular HIVconsv protein for all the tested vaccines. When administered intramuscularly to the BALB/c mice, a 2- to 3.5-fold increase in frequencies of vaccine-elicited T-cells were observed for the DNA modality, however, there was no consistent significant improvement when using a much more potent heterologous regimen of ChAdV63 prime-MVA boost. Our results concur with previous DNA studies and emphasize that immunopotentiation by the tPA-SP is likely immunogen, vaccine modality, type of immune responses and species specific. Thus, the tPA-SP effect on induction of desired immune responses should be assessed for each vaccine strategy separately.